2008
DOI: 10.1167/iovs.07-1267
|View full text |Cite
|
Sign up to set email alerts
|

Brightness, Contrast, and Color Balance of Digital versus Film Retinal Images in the Age-Related Eye Disease Study 2

Abstract: A histogram-based model, derived from exemplars, provides a pragmatic guide for image analysis and enhancement. In AREDS2, the best digital images matched the best film. Overall, however, digital provided lower contrast of retinal detail. Digital images taken with higher G-to-R ratio showed better brightness and contrast management. Optimization of images in the multicenter study helps standardize documentation of AMD (ClinicalTrials.gov NCT00345176).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 8 publications
2
73
0
Order By: Relevance
“…Digital photographs were balanced for color and contrast to closely match 35-mm fundus slides. 16 Our 2400 ϫ 2000-pixel digital photography resolving power was approximately 13 m on the retina, sufficient for detecting the smallest IRMA, NVE, or Ma seen on the film. As much as possible, we minimized differences between viewing stereo and monoscopic images.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Digital photographs were balanced for color and contrast to closely match 35-mm fundus slides. 16 Our 2400 ϫ 2000-pixel digital photography resolving power was approximately 13 m on the retina, sufficient for detecting the smallest IRMA, NVE, or Ma seen on the film. As much as possible, we minimized differences between viewing stereo and monoscopic images.…”
Section: Discussionmentioning
confidence: 92%
“…The color-balancing algorithm was modified from one included in the UW Fundus Photograph Reading Center algorithm for reading Age-Related Eye Disease Study 2 (AREDS2) digital images. 16 Digital photography from the 152 stereo pair image sets were copied and processed to create the other digital formats. Monochromatic green channel images are thought to provide better contrast of small lesions against their background than does full color photography.…”
Section: Fundus Photographsmentioning
confidence: 99%
“…Hubbard et al [60] analyzed the brightness, contrast and color balance of digital versus film retinal images to propose a model tailored for the evaluation of AMD. They considered 3-megapixel systems, at 30° FOV, as acceptable to image AMD retinas where ‘... drusen as small as 32 µm diameter ...’ can be found although resolutions over a 6-megapixel system are preferred [60].…”
Section: Influence On the Diagnosismentioning
confidence: 99%
“…They considered 3-megapixel systems, at 30° FOV, as acceptable to image AMD retinas where ‘... drusen as small as 32 µm diameter ...’ can be found although resolutions over a 6-megapixel system are preferred [60]. They concluded that ‘In AREDS2, the best digital images matched the best film.…”
Section: Influence On the Diagnosismentioning
confidence: 99%
“…1 Clinical characteristics in the 310 subjects included in the study are given in Table 1 at DCCT baseline (1983)(1984)(1985)(1986)(1987)(1988)(1989), EDIC baseline, and at the time of the digitalto-film transition study (EDIC years [14][15][16]. Comparison of the 310 participants with the remaining 1131 persons enrolled in the DCCT showed no important differences except that more nonparticipants were male, from the secondary cohort, and had higher mean hemoglobin A 1c levels during DCCT (eTable; www .archophthalmol.com), largely because 6.9% who had died and 6.2% who were inactive were included as substudy nonparticipants.…”
Section: Subjectsmentioning
confidence: 99%